Hospital use in survivors of transient ischaemic attack compared with survivors of stroke in central China: a nested case–control study. Issue 7 (9th July 2019) - Li, Sangsang; Tian, Qingfeng; Fan, Junxing; Shi, Zhan; Guo, Bingxin; Chen, Huanan; Li, Yapeng; Shi, Songhe
Abstract : Objectives: There is a lack of knowledge regarding post-discharge hospitalisation utilisation after transient ischaemic attack (TIA) in China. The aim of this study is to quantify rehospitalisation use in survivors of TIA compared with their own previous hospital use and matched survivors of stroke. Design: Nested case–control study of electronic medical records datasets. Setting: 958 hospitals in Henan, China, from July 2012 to December 2015. Participants: In total, 4823 survivors of stroke were matched to the TIA cohort (average age: 64.5 years; proportion of men: 48.4%) at a 1:1 ratio. All subjects with an onset of stroke/TIA were recorded with a 1-year look-back and follow-up. Outcome measures: Adjusted difference-in-differences (DID) values in 1-year hospital lengths of stay (LOSs) and readmission within 7, 30 and 90 days. Results: There was an increase in hospital admissions in survivors of TIA in the year after the index hospitalisation compared with the prior year. Of the 2449 rehospitalisation events that occurred during the first year after TIA, stroke (20.6%) was the most common reason for rehospitalisation. There was no difference in the stroke-specific readmission rates between the TIA and stroke cohorts (p=0.198). The TIA cohort had fewer readmissions within 30 days and 90 days after all-cause discharge compared with the controls. The corresponding covariate-adjusted DID values were −3.5 percentage points (95% CI −5.3 to −1.8) and −4.5 (95% CI −6.5 to −2.4), respectively. A similar trend was observed in the 1-year LOS. In the stratified analysis, the DID reductions were not significant in patients with more comorbidities or in rural patients. Conclusions: Compared with survivors of stroke, survivors of TIA use fewer hospital resources up to 1 year post-discharge. Greater attention to TIAs among patients with more comorbidities and rural patients may provide an opportunity to reduce hospital use.